Overall migration in plastic food packaging materials - Fabros, Lesley Maye R.
Overall migration is defined as a diffusion process in which low molecular mass substances from the packaging are being released into the contained food product. The role of food packaging to protect, preserve, and maintain the quality and safety of food would be defeated if overall migration of potentially harmful substances from the packaging become very significant. In this study, representative samples of plastic food containers from Metro Manila, commonly used as take-away food packaging, were tested for overall migration. All samples were made of polypropylene. Overall migration through article filling and immersion following the recommended food stimulants and storage conditions were conducted as per the European Union standards. Overall migration values for aqueous, acidic, alcoholic and fatty foods under simulating test conditions from frozen to boiling/retort condition varied from 0.00 to 13.21mg/dm2, 0.00 to 5.13 mg/dm2, 0.00 to 2.03 mg/dm2 and 0.52 to 0.67 mg/dm2, respectively. All samples passed the limits specified by the US FDA (0.5 mg/in2 or 7.75 mg/dm2) and EU (10 mg/dm2) for overall migration across all food stimulants except for sample A, exposed to aqueous stimulant and stored at 100ºC for 1 or 2 hr. A follow up study on specific migration is recommended for sample A, to determine what specific substances are migrating into aqueous foods. All packaging samples were considered safe to be used to store acidic, alcoholic or fatty foods.